Amber the orange fairy - Meadows, Daisy; Ripper, Georgie (New York : Scholastic, 2003)
Rainbow Fairies Rachel and Kirsty must rescue Amber, who is trapped in a seashell.
"A little Apple paperback."
RL2.
006-009.
Accelerated Reader AR
Keywords: Fairies -- Juvenile fiction; Rescues -- Juvenile fiction; Colors -- Juvenile fiction; Fairies -- Fiction; Rescues -- Fiction; Color -- Fiction; Fantasy; Fantasy fiction